Congenital syphilis in neonates: a case report - I Gede Yogi Priyatna Biantara; Romy Windiyanto (DiscoverSys Inc., 2022)
Background: Congenital syphilis (CS) in neonates is diagnosed when Treponema pallidum was identified in a laboratory test of neonates infected by mothers with syphilis. Recently, CS is still a significant and growing health problem worldwide despite being preventable. This case report will provide an overview of CS management conducted at our center, Sanjiwani Hospital, Gianyar, Bali-Indonesia. Case presentation: We report a case of CS in a newborn female neonate with the positive result of TPHA and VDRL titer 1/128 from a mother diagnosed with the latent phase of syphilis infection. On physical examination found subcostal retraction of the chest, grunting on auscultation, and jaundice. The treatments given include oxygen via cannula nasal with 2 liters per minute, intravenous access with dextrose 10%, the antibiotic combination of cefotaxime 125 mg every 12 hours and gentamicin 12.5 mg every 24 hours. For the management of CS, the patient was given Benzathine Penicillin G at a dose of 125,000 IU single dose intramuscularly. Phototherapy was assisted the patient for 48 hours to manage the hyperbilirubinemia. The patient was discharged on the eight days of treatment with oral antibiotic cefixime 12.5 mg every twelve hours for three days. Conclusion: The entity of CS is a disease suffered by infants with clinical manifestations or examination supporting the diagnosis of syphilis. The mother should do a screening during her pregnancy to prevent untreated syphilis and its complications for her babies.